Preparation method and application of nano silicon carbide
Nanosilicon carbide is prepared by two-step low-temperature thermal reduction and calcination, which solves the problem of high reaction temperature and difficult to control the dimensional morphology in the carbon thermal reduction method, and achieves efficient preparation of nanosilicon carbide as the negative electrode material of lithium-ion batteries, improving cycle stability and electrochemical performance.
Patent Information
- Application Number
- CN202411829858.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The preparation of nano-silicon carbide by carbon thermal reduction method has a high reaction temperature, which makes it difficult to control the size and morphology, and it is necessary to obtain the ideal particle size through mechanical crushing and screening.
The two-step process of low-temperature thermal reduction combined with calcination is used to achieve rapid low-temperature reduction using molten salt and hydride system, and then a silicon carbide composite is formed with petroleum-based hydrocarbons, and nano silicon carbide is generated by calcination at a lower temperature.
The reaction temperature was greatly reduced relative to the carbon thermal reduction method, and 3C crystal nano silicon carbide with uniform size and uniform morphology was prepared. It was used as the negative electrode material for lithium-ion batteries, improving cycle stability and electrochemical performance.
Smart Images

Figure CN119637878A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a preparation method and application of nano silicon carbide. Technical Background
[0002] Silicon carbide is an inorganic substance with the chemical formula SiC. It has stable chemical properties, high thermal conductivity, low thermal expansion coefficient, and good wear resistance. It is mainly used to manufacture abrasives, wear-resistant agents, abrasive tools, and advanced refractory materials. It is also used to manufacture fine ceramics and electronic devices. In particular, in the third-generation semiconductor materials, silicon carbide has attracted attention due to its excellent electrical properties. In addition, silicon carbide materials are also used in the biomedical field. Due to its biological inertness, it can be used in organisms without causing adverse reactions.
[0003] Nano-SiC particle size ranges from 50nm to 500nm, with high specific surface area and high reactivity. It has a wide range of applications in many fields, including semiconductor devices, optical components, biomedical materials, environmental protection, electromagnetic shielding materials, high-performance coatings, lithium-ion battery negative electrode materials, etc., which are widely used in semiconductor devices. In terms of the process methods for preparing nano-SiC, it is divided into carbon thermal reduction, laser-induced gas phase reaction synthesis, thermal chemical gas phase reaction method (CVD method), plasma method, etc. Among them, the carbon thermal reduction method uses quartz stone and petroleum coke as silicon source and carbon source respectively, which needs to be heated to above 2500℃ so that petroleum coke reduces quartz, and by adjusting the parameters such as the type of reactants, heating method, heating temperature and insulation time, the purity and particle size of the generated nano-SiC can be controlled. The carbon thermal reduction method has low raw material cost and simple reaction requirements, and is suitable for large-scale production of nano-SiC with higher purity. However, the carbon thermal reduction method for preparing nano-SiC has the problem of too high reaction temperature (above 2500℃), and the high temperature reaction makes it difficult to control the size and morphology of SiC. Mechanical crushing and screening are often required to obtain the desired particle size.
[0004] Molten salt is a liquid state formed after melting at high temperature. It is widely used as a reaction medium in the fields of material synthesis, surface treatment and metal extraction. In the study of magnesium thermal reduction of silicon dioxide to prepare elemental silicon, adding AlCl3 as a molten salt in the reaction system can reduce the reaction temperature from 680℃ to 250℃. On the one hand, AlCl3 provides a liquid environment for the magnesium thermal reduction reaction, and on the other hand, AlCl3 reacts with silicon dioxide to produce SiCl4. Therefore, the molten salt reaction system can reduce the reduction temperature of silicon dioxide.
[0005] As the demand for renewable energy continues to grow, secondary batteries have ushered in new opportunities in the energy revolution. Among them, the global production and manufacturing scale of lithium-ion batteries has reached an unprecedented level, which has also led to in-depth research on lithium-ion battery negative electrode materials. Silicon-based negative electrodes have extremely high theoretical specific capacity (3579mAh g -1 For Si lithiation to Li 3.75 Si, 4200mAh g -1 Lithiation of Si to Li 4.4 However, the lithium-insertion and deinsertion cycle causes the silicon material to have a serious volume expansion, so pure silicon material cannot be used alone as a lithium battery negative electrode material. Silicon-carbon or silicon carbide composites are increasingly used in lithium-ion batteries due to their low cost, simple synthesis methods, easy availability, sustainable strategies and improved battery performance (including capacity, cycle performance and stability / durability). Summary of the invention
[0006] Purpose of the invention: The technical problem to be solved by the present invention is that the reaction temperature of preparing nano silicon carbide by carbon thermal reduction method is too high (above 2500°C), and the high temperature reaction makes it difficult to control the size and morphology of silicon carbide. Mechanical crushing and screening are often required to obtain the ideal particle size. The prepared nano silicon carbide, as the negative electrode of lithium ion battery, improves the cycle stability of lithium ion battery.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing nano silicon carbide material comprises the following steps:
[0009] (1) mixing a silicon-containing compound, a hydride, a molten salt and a petroleum-based hydrocarbon, adding the mixture to a reactor, and heating the mixture in an argon environment; washing, filtering and drying the product obtained by the low-temperature thermal reduction reaction to obtain brown particles;
[0010] (2) The brown particles obtained in step (1) are calcined in an argon environment, and the product is obtained after drying and simple grinding.
[0011] Specifically, in step (1), the selected silicon-containing compound is one of silicon dioxide, rice husk white carbon black, methyl silicone oil, water glass
[0012] Specifically, in step (1), the molten salt is one or a combination of aluminum chloride, potassium chloride, calcium chloride or sodium chloride.
[0013] Specifically, in step (1), the hydride is one or a combination of sodium hydride, calcium hydride, magnesium hydride, and lithium hydride.
[0014] Specifically, in step (1), the petroleum-based hydrocarbon is one of asphalt coke, coal tar, coal tar, and paraffin.
[0015] Specifically, in step (1), the selected molten salt can be one or a combination of aluminum chloride, potassium chloride, calcium chloride or sodium chloride, the mass ratio of the nano-silicon dioxide, hydride, molten salt, and petroleum-based hydrocarbon is in the range of 1: (1-4): (15-20): (1-4), in an argon environment, the reaction temperature is 250-300°C, the reaction time is 0.5-1 hour, and the insulation time is 1-4 hours. The washing and drying treatment is washing with distilled water 3 times and vacuum drying at 60°C for 1 hour.
[0016] Specifically, in step (2), under an argon environment, the temperature is raised to 1200-1600° C. at a heating rate of 5-10° C. / min and maintained for 1-4 hours, and then cooled to room temperature at a cooling rate of 5-10° C. / min.
[0017] Specifically, in step (2), the powder is simply ground manually, and the particle size of the powder after sieving is less than 200 mesh.
[0018] Furthermore, the nano-silicon carbide prepared by the above preparation method is also within the protection scope of the present invention.
[0019] Furthermore, the present invention also claims to protect the use of the prepared nano-silicon carbide as a negative electrode material for lithium-ion batteries.
[0020] Furthermore, the present invention also claims protection for a lithium-ion battery, the negative electrode material of which is prepared using the nano-silicon carbide prepared above.
[0021] Beneficial effects:
[0022] (1) The present invention prepares nano-silicon carbide by a two-step method of low-temperature reduction combined with calcination, using a system of molten salt and hydride to achieve rapid low-temperature reduction of silicon-containing compounds (reaction temperature below 300°C, reaction time 0.5 to 1 hour), and generate carbon-silicon composites with petroleum-based hydrocarbons; then calcining at a relatively low temperature (1200 to 1600°C) to generate nano-silicon carbide. Compared with carbothermal reduction, the reaction temperature is greatly reduced.
[0023] (2) The present invention prepares 3C crystalline nano-silicon carbide by a two-step method of low-temperature reduction combined with calcination. The morphology is uniform in the form of particles with obvious edges and corners, and the size is 10 to 20 nm. The size is uniform, avoiding the complex process of controlling the product morphology and particle size by changing the reaction conditions, and no mechanical crushing and screening are required.
[0024] (3) As a negative electrode material for lithium-ion batteries, the product of the present invention has a high reversible specific capacity, good cycle stability, and excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0026] Figure 1 This is a transmission electron microscope image of the lithium-ion battery negative electrode material prepared in Example 1.
[0027] Figure 2 These are the X-ray diffraction patterns of Example 1 (SC-1500), Example 4 (SC-1200), Example 5 (SC-1300), Example 6 (SC-1400) and Example 7 (SC-1600).
[0028] Figure 3 The first ten cycles of the cyclic voltammetry curve of the lithium ion battery negative electrode material prepared in Example 1.
[0029] Figure 4 The impedance diagram of the negative electrode materials for lithium-ion batteries prepared in Example 1 (SC-1500), Example 6 (SC-1400), and Example 7 (SC-1600) at a frequency of 100,000 to 0.01 Hz after 50 cycles of charge and discharge.
[0030] Figure 5 This is the charge and discharge curve of the lithium ion battery negative electrode material prepared in Example 1 at a current density of 0.01 A / g and the first charge and discharge three times.
[0031] Figure 6 The lithium-ion batteries prepared in Example 1 (SC-1500), Example 6 (SC-1400), and Example 7 (SC-1600) were charged and discharged three times at a current density of 0.01 A / g for the first time, and then cycled 200 times at a current density of 0.05 A / g.
[0032] Figure 7 This is a rate performance diagram of the lithium-ion battery prepared in Example 1 at different current densities. DETAILED DESCRIPTION
[0033] The present invention can be better understood with reference to the following examples. Example 1
[0034] Take 2g of silica, add silica, calcium hydride, aluminum chloride, and asphalt coke into the reactor in a mass ratio of 1:2:15:1, the reaction temperature is 250℃, the reaction time is 0.5 hours, and the insulation time is 2.5 hours. Wash the reaction product with distilled water 3 times, and vacuum dry it at 60℃ for 1 hour. Put the dried product into a tubular furnace, heat it to 1500℃ at a heating rate of 5℃ / min and keep it for 2h, then cool it to room temperature at a cooling rate of 10℃ / min. Take out the sample and grind it to obtain the negative electrode material of lithium-ion battery. (SC-1500) Example 2
[0035] Take 2g of silicon dioxide, the molten salt is a mixture of 84% aluminum chloride / 10% sodium chloride / 6% potassium chloride, add silicon dioxide, calcium hydride, molten salt, and asphalt coke into the reactor in a mass ratio of 1:2:15:1, and the molten salt is a reaction temperature of 250°C, a reaction time of 0.5 hours, and a holding time of 2.5 hours. Wash the reaction product with distilled water three times and vacuum dry it at 60°C for 1 hour. Put the dried product into a tubular furnace, heat it to 1500°C at a heating rate of 10°C / min and keep it for 2h, then cool it to room temperature at a cooling rate of 10°C / min. Take out the sample and grind it to obtain the negative electrode material of the lithium-ion battery. Example 3
[0036] Take 2g of silicon dioxide, add silicon dioxide, sodium hydride, aluminum chloride, and asphalt coke into the reactor in a mass ratio of 1:4:15:1, the reaction temperature is 250℃, the reaction time is 0.5 hours, and the insulation time is 2.5 hours. Wash the reaction product with distilled water 3 times and vacuum dry it at 60℃ for 1 hour. Put the dried product into a tubular furnace, heat it to 1500℃ at a heating rate of 5℃ / min and keep it for 2h, then cool it to room temperature at a cooling rate of 10℃ / min. Take out the sample and grind it to obtain the negative electrode material of lithium-ion battery. Example 4
[0037] Take 2g of rice husk silica, add rice husk silica, sodium hydride, aluminum chloride, and coal tar into the reactor in a mass ratio of 1:4:15:2, the reaction temperature is 250℃, the reaction time is 0.5 hours, and the insulation time is 2.5 hours. Wash the reaction product with distilled water 3 times and vacuum dry it at 60℃ for 1 hour. Put the dried product into a tubular furnace, heat it to 1200℃ at a heating rate of 5℃ / min and keep it for 2h, then cool it to room temperature at a cooling rate of 10℃ / min. Take out the sample and grind it to obtain the negative electrode material of lithium-ion battery. (SC-1200) Example 5
[0038] Take 2g of silica, add silica, magnesium hydride, aluminum chloride, and asphalt coke into the reactor in a mass ratio of 1:2:15:1, the reaction temperature is 250℃, the reaction time is 0.5 hours, and the insulation time is 2.5 hours. Wash the reaction product with distilled water 3 times, and vacuum dry it at 60℃ for 1 hour. Put the dried product into a tubular furnace, heat it to 1300℃ at a heating rate of 5℃ / min and keep it for 2h, then cool it to room temperature at a cooling rate of 10℃ / min. Take out the sample and grind it to obtain the negative electrode material of lithium-ion battery. (SC-1300) Example 6
[0039] Take 2g of dimethyl silicone oil, add dimethyl silicone oil, sodium hydride, aluminum chloride, and paraffin into the reactor in a mass ratio of 1:4:15:2, the reaction temperature is 250℃, the reaction time is 0.5 hours, and the insulation time is 2.5 hours. Wash the reaction product with distilled water 3 times, and vacuum dry it at 60℃ for 1 hour. Put the dried product into a tubular furnace, heat it to 1400℃ at a heating rate of 5℃ / min and keep it for 2h, then cool it to room temperature at a cooling rate of 10℃ / min. Take out the sample and grind it to obtain the negative electrode material of lithium-ion battery. (SC-1400) Example 7
[0040] Take 2g of silica, add silica, calcium hydride, aluminum chloride, and asphalt coke into the reactor in a mass ratio of 1:2:20:1, the reaction temperature is 250℃, the reaction time is 0.5 hours, and the insulation time is 2.5 hours. Wash the reaction product with distilled water 3 times, and vacuum dry it at 60℃ for 1 hour. Put the dried product into a tubular furnace, heat it to 1600℃ at a heating rate of 5℃ / min and keep it for 2h, then cool it to room temperature at a cooling rate of 10℃ / min. Take out the sample and grind it to obtain the negative electrode material of lithium-ion battery. (SC-1600)
[0041] Figure 1 These are two transmission electron microscope images of the lithium-ion battery negative electrode material prepared in Example 1 at different magnifications. As can be seen from Figure a, the product silicon carbide is granular, with obvious edges and corners, and a size of 10 to 20 nm, with uniform size. Figure b is an enlarged crystal structure, with a flat crystal surface and an obvious silicon carbide lattice spacing of d = 0.14 nm, proving that the silicon carbide material was successfully prepared. Figure 2The X-ray diffraction patterns of Example 1 (SC-1500), Example 4 (SC-1200), Example 5 (SC-1300), Example 6 (SC-1400) and Example 7 (SC-1600) show the silicon carbide formation process at different temperatures. Among them, the three materials of Examples 1, 6 and 7 have diffraction peaks at 35.6, 41.5, 60, 71.8 and 75.4°, corresponding to the (111), (200), (220), (311) and (222) crystal planes of silicon carbide. There is a small peak at about 34°, which is the stacking fault of silicon carbide. There are no impurity peaks in the image, which proves that high-purity silicon carbide material can be generated after 1400°C. Figure 3 The cyclic voltammetry curves of the first ten cycles of the negative electrode material for lithium-ion batteries prepared in Example 1 are shown. From the first cycle to the second cycle, it can be seen that the SEI film disappears significantly. The two oxidation peaks at ≈0.2 and ≈1 V can be attributed to Li + of extraction. Figure 4 The lithium-ion battery negative electrode materials prepared in Example 1 (SC-1500), Example 6 (SC-1400), and Example 7 (SC-1600) are impedance diagrams at a frequency of 100,000 to 0.01 Hz after 50 cycles of charge and discharge. From the comparison of the figures, it can be seen that the silicon carbide negative electrode material prepared at 1500°C has relatively better conductivity. Figure 5 As shown, it was determined that the discharge capacity of the lithium ion battery negative electrode material prepared in Example 1 was 777.38 mAh / g at a current density of 0.01 A / g, and the initial coulombic efficiency was 35.8%. Figure 6 From the lithium-ion batteries prepared with the three materials of Example 1 (SC-1500), Example 6 (SC-1400), and Example 7 (SC-1600), after the first charge and discharge three times at a current density of 0.01 A / g, and then 200 cycles at a current density of 0.05 A / g, it can be seen that the silicon carbide negative electrode material prepared at 1500°C has a higher relative capacity, and the capacity retention rate is 104.59% at a current density of 0.05 A / g, and the capacity has increased slightly. Figure 7 This is a rate performance diagram of the lithium-ion battery prepared in Example 1 at different current densities. It can be seen from the tests at different current densities that the material has a high capacity retention rate and good rate performance.
[0042] The present invention provides a method for preparing nano silicon carbide and an idea and method for its application. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A preparation method and application of nano silicon carbide, characterized in that: The steps include: (1) mixing a silicon-containing compound, a hydride, a molten salt and a petroleum-based hydrocarbon, adding the mixture to a reactor, and heating the mixture in an argon environment; washing, filtering and drying the product obtained by the low-temperature thermal reduction reaction to obtain brown particles; (2) The brown particles obtained in step (1) are calcined in an argon environment, and the product is obtained after drying and simple grinding.
2. The preparation method and application of nano-silicon carbide according to claim 1, characterized in that: In step (1), the silicon-containing compound is one of silicon dioxide, rice husk white carbon black, methyl silicone oil and water glass.
3. The preparation method and application of nano-silicon carbide according to claim 1, characterized in that: In step (1), the molten salt is one or a combination of aluminum chloride, potassium chloride, calcium chloride or sodium chloride.
4. The preparation method and application of nano-silicon carbide according to claim 1, characterized in that: In step (1), the hydride is one or a combination of sodium hydride, calcium hydride, magnesium hydride, and lithium hydride.
5. The preparation method and application of nano-silicon carbide according to claim 1, characterized in that: In step (1), the petroleum-based hydrocarbon is one of asphalt coke, coal tar, coal tar, and paraffin.
6. The preparation method and application of nano-silicon carbide according to claim 1, characterized in that: In step (1), the mass ratio of the nano-silicon dioxide, hydride, molten salt, and petroleum-based hydrocarbon is in the range of 1: (1-4): (15-20): (1-4). In an argon environment, the reaction temperature is 250-300° C., the reaction time is 0.5-1 hour, and the insulation time is 1-4 hours. The washing and drying treatments are washing with distilled water for 3 times and vacuum drying at 60° C. for 1 hour.
7. The preparation method and application of nano-silicon carbide according to claim 1, characterized in that: In step (2), in an argon environment, the temperature is raised to 1200-1600° C. at a heating rate of 1-10° C. / min and maintained at that temperature for 1-4 hours, and then cooled to room temperature at a cooling rate of 5-10° C. / min.
8. The preparation method and application of nano-silicon carbide according to claim 1, characterized in that: In step (2), the powder is simply ground manually, and the powder particle size after sieving is less than 200 mesh.
9. Nano-silicon carbide prepared by any one of the preparation methods of claims 1 to 7.
10. Use of the nano silicon carbide according to claim 8 as a negative electrode material for lithium ion batteries.
11. A lithium ion battery, characterized in that: The negative electrode is prepared by using the nano silicon carbide described in claim 7.
Citation Information
Patent Citations
Novel process and product
CN106573775A
Green method for preparing beta-silicon carbide with high specific surface area
CN113666375A
Nano silicon material prepared by low-temperature molten salt thermal method and preparation method and application thereof
CN115465864A
Preparation method of beta-SiC powder
CN116102016A
Preparation method of silicon-carbon negative electrode material and application of silicon-carbon negative electrode material as lithium ion battery electrode
CN117566743A